A Widow's karma. - Leong, Sheu Ying. (2009)
This report gives an overview for the photojournalism project titled "A Widow's Karma" by providing information on the background of the subject. Other areas that are covered include the process undertaken to produce both the book and the exhibition, the insights gained and the challenges faced while working on this project.